ANALISIS QUALITY OF SERVICE (QOS) PADA JARINGAN INTERNET (STUDI KASUS : FAKULTAS KEDOKTERAN UNIVERSITAS TANJUNGPURA) - Sasmita, Wahyu Patrya; Safriadi, Novi; Irwansyah, M Azhar (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Quality of service is theability of a network to provide better serviceto serve network traffic that passing throughit. From the results of a survey conducted bytaking a sample of the 2040 Quality ofService (QoS) for 16 days, the Internetnetwork at the Faculty of Medicine,University of Tanjungpura get value of 2.33at SSID Hotspot_FK and 2.53 at SSIDHotspot_FK2 with a standard category Fairin Telecommunications and InternetProtocol Harmonization Over Networks(TIPHON). For the average DownloadSpeed on SSID Hotspot_FK amounted to252.53 Mbps and 871.71 Mbps for SSIDHotspot_FK2. As for the average UploadSpeed on SSID Hotspot_FK amounted to99.19 Mbps and 372.55 Mbps for SSIDHotspot_FK2. Applications that used in themeasurement is the command prompt,wireshark, and google chrome which refersto the site speedtest.biznetworks.com andwww.pingtest.net. And the measurementresults can indicate the QoS parametervalues consists of packet loss, delay, jitter,throughput, and mean opinion source.Factors that could influence the networkQoS is attenuation, distortion, noise andbandwidth capacity